2004
DOI: 10.1007/s00774-003-0459-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial of risedronate in Japanese volunteers: a study on the effects of timing of dosing on absorption

Abstract: Because of its chemical structure, risedronate was thought to form a complex with divalent cations, e.g., Ca(2+), and to be likely to show changes in the efficiency of absorbance from the gastrointestinal tract according to the presence of food. Therefore, we conducted a crossover study using healthy Japanese adults to examine the effects of food intake on absorption after the oral administration of risedronate and to choose the best timing of regimen for risedronate. Using single doses of 5 mg risedronate, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…The oral drug absorption under the fed state can be more or less than that under the fasted state, which are often called positive and negative food effects, respectively. [5][6][7][8] Fleisher et al stated that drugs classified into class I, class II and class III using the biopharmaceutics classification system (BCS) are likely to be not affected by food, be positively affected by food and be negatively affected by food, respectively, while the effects are unclear for class IV drugs. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The oral drug absorption under the fed state can be more or less than that under the fasted state, which are often called positive and negative food effects, respectively. [5][6][7][8] Fleisher et al stated that drugs classified into class I, class II and class III using the biopharmaceutics classification system (BCS) are likely to be not affected by food, be positively affected by food and be negatively affected by food, respectively, while the effects are unclear for class IV drugs. …”
mentioning
confidence: 99%
“…The oral drug absorption under the fed state can be more or less than that under the fasted state, which are often called positive and negative food effects, respectively. [5][6][7][8] Fleisher et al stated that drugs classified into class I, class II and class III using the biopharmaceutics classification system (BCS) are likely to be not affected by food, be positively affected by food and be negatively affected by food, respectively, while the effects are unclear for class IV drugs. 9) As the main cause of the positive food effect, it is considered that the ingestion of food stimulates the secretion of bile juice into the gastrointestinal tract, which accelerates the solubility and dissolution of poorly water-soluble drugs and then enhances oral absorption.…”
mentioning
confidence: 99%
“…Recently, some studies reported that a low dose of bisphosphonates can be as effective as higher doses, particularly in Asians when compared with Caucasians 25) . Gertz et al 26) reported that the cumulative urinary clearance rate of a 10-mg dose of alendronate was 0.4% in Caucasian women, which was similar to the values in Korean (0.48%) and Japanese (0.43%) women who were administered half the dose (5 mg) of alendronate 27,28) .…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis in Japanese women may be adequately treated with smaller risedronate doses than those used to treat Caucasian women . This difference in the effectiveness of risedronate treatment between two ethnicities may be due to differences in the pharmacokinetics of risedronate (Ogura et al 2004) and/or genetic factors (Eisman 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The maximum plasma concentration and the area under the plasma concentration-time curve up to 24 hr after oral administration of risedronate were previously reported to be 2-3-fold higher in Japanese subjects than in Caucasian subjects (Ogura et al 2004). Therefore, the recommended dosage of risedronate is 2.5 mg for Japanese, compared with 5.0 mg for Caucasians.…”
Section: Study Population and Designmentioning
confidence: 99%